2014
DOI: 10.1038/ki.2014.62
|View full text |Cite
|
Sign up to set email alerts
|

The high-mobility group protein B1–Toll-like receptor 4 pathway contributes to the acute lung injury induced by bilateral nephrectomy

Abstract: Acute lung injury and acute kidney injury are severe complications in critically ill patients and synergistically increase mortality in intensive care units. Organ cross-talk between the kidney and the lung has been implicated recently as amplifying injury in each organ. Here we sought to identify a possible mechanism of acute kidney injury-induced acute lung injury using a mouse bilateral nephrectomy model. Toll-like receptor 4 (TLR4)-mutant C3H/HeJ mice were more resistant to lung injury including neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 47 publications
1
58
0
Order By: Relevance
“…Results of recent animal experiments demonstrated that an acute decline of renal function caused by ischemia reperfusion or bilateral nephrectomy increases many inflammatory mediator levels in blood, such as interleukin-6 and high-mobility group protein B1 (HMGB1) [17,18,19,20]. In a sepsis model of cecal ligation and puncture, pre-existing renal dysfunction worsened survival by increasing blood high HMGB1 and vascular endothelial growth factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of recent animal experiments demonstrated that an acute decline of renal function caused by ischemia reperfusion or bilateral nephrectomy increases many inflammatory mediator levels in blood, such as interleukin-6 and high-mobility group protein B1 (HMGB1) [17,18,19,20]. In a sepsis model of cecal ligation and puncture, pre-existing renal dysfunction worsened survival by increasing blood high HMGB1 and vascular endothelial growth factor [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Renal replacement therapy (RRT) requirement in septic shock patients with severe AKI is particularly a strong predictive factor for mortality [16]. Biologically, severe AKI has been suggested to amplify the sepsis cascade induced by endotoxin [17,18,19,20,21,22]. Therefore, it can be hypothesized that removing endotoxin is more beneficial for septic shock patients complicated with AKI than those without that complication.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated increased blood high-mobility group protein B1-induced lung injury via toll-like receptor 4 in another mouse AKI model of bilateral nephrectomy. 34 Second, IR injury to one organ might cause systemic reaction, possibly mediated by inflammatory cytokines or cells. Andrés-Hernando and colleagues reported that proinflammatory cytokines IL-6, chemokine (C-X-C motif) ligand 1, IL-1b, and TNF-a were increased not only in the kidney, but in the spleen and liver in renal IR injury.…”
Section: Discussionmentioning
confidence: 99%
“…34,41 Quantification of gene expressions was calculated relative to b-actin. Amplification data were analyzed using software (Prism Sequence Detection System version 2.1; Applied Biosystems, Foster City, CA).…”
Section: Real-time Pcr Assay For Tnf-a Expression In the Heartmentioning
confidence: 99%
“…In a previous study, TLR4 was demonstrated to act as a negative regulator of noninfectious lung inflammation induced by low-molecular-weight hyaluronic acid (25). Furthermore, Doi et al (26) established an ALI model using TLR4-mutant (C3H/HeJ) mice and TLR4-wild-type (C3H/HeN) mice, and the results indicated that C3H/HeJ mice had significantly decreased expression levels of inflammatory cytokines and were protected against ALI. It has been reported that TLR4 deficiency not only inhibits the formation of autophagosomes, but also results in decreased numbers of autophagosomes in lung tissue (24).…”
Section: Discussionmentioning
confidence: 99%